A Study on Soil Thermophilic and Thermotolerant Fungi in Thamar-Yemen - Al-Bader, Salah M.; Aleryani, Adel Q.; Almutaa, Aisha (Arab Journal for Sciences and Research Publishing, 2017)
Thirty-eight soil samples were collected from different sites in Thamar province during the period from 4/2012 to 2/2013.The direct plate, and dilution plates methods were followed to isolation of counting colony forming units, the potato carrot agar (PCA) and Emerson's media were used A total of 23 fungi belong to (14) genera were isolated, they include (11) Hyphomycetes, (10) Ascomycetes, and (2) Zygomycetes besides black and white sterile mycelium. A fourteen  isolates were regarded asnewly record for Yemeni mycobiota,they include Acremonium murorum, Acrophialophorafusispora, Chaetomiumatrobrunneum, C.gracile,C.strumarium, C.therophilevar.coprophpile, Corynascussepedonium ,Emericellarugulosa, Melanocarpusalbomyces, paecelomycesinflatus Papulosporathermophila, Rhizomucormiehi, Scytalidiumthermophilum, and Talromycesthermophilus Soil dilution method showed that the  colony forming units (CFUs)in soil had seasonal fluctuation , they were significantly  higher (36667)  during moderate/humid month than  cold/dry months (20400) (p
Keywords: Fungi; Thermophilic; Soil; Enzyme; Yemen; Seasonal fluctuation